Analisis Perbedaan Regulasi Pangan pada Pasar Ekspor: Studi Kasus Penarikan Produk Mi Instan Indonesia di Beberapa Negara - Rindu Aprillia; Halimah Zahrah; Wulan Nur Aszad; Zahra Fauziahsari (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study examines how differences in food safety regulations in Indonesia, Taiwan, and Malaysia impacted the recall of Indomie Special Chicken Flavor products in Taiwan and Malaysia. The main issue revealed is that regulatory differences led to the recall of the product, even though it met applicable Indonesian food safety standards and Codex Alimentarius standards. This study aims to identify the factors contributing to the recall and provide strategic recommendations to industry stakeholders. Employing descriptive qualitative methods and literature analysis, this study investigates the product recall caused by ethylene oxide (EtO) levels exceeding limits set by Taiwanese and Malaysian authorities. The results indicate that differences in export destination country regulations are a key factor in product recalls, requiring producers to understand and comply with local regulations more thoroughly. Additionally, the study emphasizes the importance of business ethics and transparent crisis communication strategies for maintaining corporate reputation and consumer trust. These findings offer strategic recommendations to industry stakeholders and policymakers for managing regulatory compliance and risk mitigation to ensure the sustainability of Indonesian food exports to global markets. Thus, this study contributes to a better understanding of international regulatory dynamics and their implications for the food industry.